Brand Image and its Research - Ruževičius, Juozas; Savkova, Anastasija (Ekonomika, 2003)
At the time of world economical integration and competition becoming stronger, effective management of quality and its means of identification (trade and quality marks, brands etc.) system becomes one of the most important factors of company activity success in national, regional and world markets. Quality is no less important for company as well as for all the state image creating. No randomly in National quality program of the years 2004-2006 quality and image creating of Lithuanian products is considered as one of the most priority activity areas of state and business organisations. Lithuanian products and services unified trade mark “Best of Lithuania” program of Lithuanian confederation of industrialists works for this aim as well.Lithuanian products arc delivered to well-known foreign companies such as “Nike”, “c&A”, “Philips”, “Samsung”, “Renault”, “Carrefour” and many other. However it is necessary to note that major Lithuanian exporters (“Audimas”, “Audėjas”, “Utenos trikotažas”, “Snaige” JSC, etc.) export part of production with well-known foreign companies brands. Therefore image creating of Lithuanian products and its spread abroad is especially important.The purpose of article is to determine concepts of products means of identification matter and relation, to emphasize brand creating and management processes contents and features, to analyse the most important aspects of brand image creating.Above-mentioned questions are not system considered in scientific literature of our country, quite a lot of terminology confusion of this area is there in study aids and other publications in Lithuanian language. Lithuanian terminology questions of the considered problem are analysed in this paper as well.Relations and features of the elements of products identification means system such as trade mark, brand, brand symbol, company name and logotype arc emphasized and described in this article. Special attention is given to brand formation and management (branding) process features, components of this process and their management. Brand image creating theoretical and methodical questions as well as the role of trade marks and brands in corporate identity are analysed.The scientific research of particular product’s brand image was carried out. Questionnaire was prepared to test consumers and to determine the brand image of Lithuanian yoghurt “BIOS”. The results of research were processed using mathematical statistical and other methods such as standard deviation, Likert scale, semantic differential scale, rank order scaling etc.Authors make conclusion, that quality does not need image - whereas product’s image needs quality.One of the means of Lithuanian products image creating is more effective use of trade marks afforded opportunities, purposeful creation and management of products and brands, support of those initiatives on national scale and propagation of foregoing means in business world. No less actual are theoretical and methodical research of above questions.The most important results of this paper are summed in 2 tables and 7 pictures.